True or False – Difficulties in Interpreting the Funeral Dress from the Burial of the “Bride” in the Szczuczyn Crypt, Poland - Dobek, Mikołaj (Analecta Archaeologica Ressoviensia, 2022)
Funeral costumes are elements of funerary furnishings with very different characteristics. Their form was influenced not only by local funeral customs but also by the property status of the families of deceased people and the fashion trends prevailing in a given region. The study of funerary clothing clearly translates into the general development of knowledge about the evolution of fashion, and thus the issue is no longer only the domain of costumists, but also archeology. This is clearly visible on the example of the results of archaeological research conducted in the crypts of the Church of St. Name of the Blessed Virgin Mary - over 100 burials turned out to be hiding the largest archaeological collection of modern funerary clothing from the former Polish-Lithuanian Commonwealth. Against the background of these costumes, the clothes in which the woman was placed in burial no. 8 (EA crypt) stands out. Her attire took an exceptionally impressive form, as evidenced by the fact that this tomb aroused the interest of the local population long before the archaeologists arrived in Szczuczyn. According to the stories of the locals, she was buried in a wedding dress. As a result of the verification carried out both on the stand and as a result of laboratory analyzes, it was diagnosed whether this theory can be confirmed with the use of scientific methods. The analyzes, apart from referring to the theory of stories told by local history enthusiasts, turned out to contribute a lot to the current state of knowledge on the development of 18th-century women's fashion.